The intersection of heart failure and cancer in women: a review - Tyebally, Sara; Sia, Ching-Hui; Chen, Daniel; Abiodun, Aderonke; Dalakoti, Mayank; Chan, Po Fun; Koo, Chieh-Yang; Tan, Li Ling (Frontiers in Cardiovascular Medicine, 2024)
Cancer and cardiovascular disease represent the two leading causes of morbidity and mortality worldwide. Women continue to enjoy a greater life expectancy than men. However, this comes at a cost with more women developing diabetes, hypertension and coronary artery disease as they age. These traditional cardiovascular risk factors not only increase their lifetime risk of heart failure but also their overall risk of cancer. In addition to this, many of the cancers with female preponderance are treated with potentially cardiotoxic therapies, adding to their increased risk of developing heart failure. As a result, we are faced with a higher risk population, potentially suffering from both cancer and heart failure simultaneously. This is of particular concern given the coexistence of heart failure and cancer can confer a worse prognosis than either a single diagnosis of heart failure or cancer alone. This review article explores the intersection of heart failure and cancer in women at multiple levels, including traditional cardiovascular risk factors, cardiovascular toxicity derived from antineoplastic and radiation therapy, shared pathophysiology and HF as an oncogenic process. This article further identifies opportunities and strategies for intervention and optimisation, whilst highlighting the need for contemporary guidelines to better inform clinical practice.